An investigation of the C-Ni-V ternary phase diagram and development of abrasion-resistant alloys - Apata, Ayodeji Oluwatoyin (My University, 2016)
This study investigated the C-Ni-V ternary phase diagram and identification of possible abrasive-resistance alloys. Twenty-four alloys were made from the elemental components and were arc-melted under an argon atmosphere, using Ti as an oxygen-getter. These alloys were analysed in both the as-cast condition, and after annealing for 1000oC and water quenching. Microstructural characterization was carried out in a SEM with EDX, and was done to confirm the phases. The results were used to plot a solidification projection and all binary phases extended into ternary, except for ~Ni8V, ~NiV3 and ~V2C which were not found, due to the sample compositions chosen. The extensions of the binary phases were: ~Ni3V: ~15 at.% C; ~Ni2V: ~20 at.% C; σ′: ~18 at.% C; (Ni): ~27 at.% C; ~V8C7: ~2 at.% Ni; ~V6C5: ~2 at.% Ni and ~VC: ~2 at.% Ni. The liquidus surface was derived, and three ternary invariant reactions were identified. The isothermal section at 1000oC was also constructed. Hardness of the alloys was studied in both conditions. Alloys with (Ni) (188-402HV5) were found to be ductile with low hardness. Alloys containing (V), ~Ni3V and ~Ni2V were identified as hard phases (533-1052 HV5). Alloys with σ′ phase were very hard (1065-1266 HV5) extremely brittle with cracks. Fracture toughness of the C-Ni-V alloys 0.9-5.2 (MPa.m-1/2) were comparable with ceramics 0.5-5.3(MPa.m-1/2). The wear behaviour of the alloys was characterized by sliding the carbide alloys against a Cr-steel ball in a pin-on-disc configuration. There were several co-existing wear mechanisms: abrasion, adhesion and the formation of a thin tribolayers. The wear coefficients for a 10N contact load after a sliding wear path of 300m varied between 0.1 x 10-6and 7.6 x 10-6(mm3/Nm), which was not as good as WC-Co hard metals, but close.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering (Metallurgy and Materials Engineering). Johannesburg, March 2014
Keywords: Physical metallurgy; Alloys; Alloys--Analysis; Phase diagrams